Livestock Diseases and Health Care Facilities in Sundarbans Delta of India - Samares Kumar Das, Hema Tripathi (Indian Journal of Extension Education, 2022)
A number of diseases attack livestock in our countryside, many of which are highly seasonal in nature. Therefore, understanding the disease pattern and health care facilities of a locality has an implication in formulating an efficient and effective disease management strategy. Thus a study was conducted in four villages of Sundarbans delta of India to understand the prevalence of livestock diseases, their seasonality, and veterinary services available. Data were collected using semi-structured interview, listing, narrative and observation. Study reveals that foot and mouth disease, Ranikhet disease, chicken pox, hump sore, etc were highly seasonal. Whereas amphistomiasis, delayed expulsion of placenta, dystokia, etc were not. Quacks, veterinary officers, medicine pedlars, medicine shop keepers, midwives, and ethnoveterinarians were the veterinary service providers in the study area. Study concludes that a holistic research is needed on documentation and validation of major livestock diseases in order to suggest effective disease management practices within the context of prevailing health care practices and available veterinary facilities.